PENGARUH MEDIA SOSIAL TERHADAP GAYA HIDUP MAHASISWA DI PALANGKA RAYA KECAMATAN JEKAN RAYA - Yosi Piani; Wiwin Pahlentesa; Indirasari Divayu Gantini; Elia Damayanti (Jurnal Sosiologi UPR, 2025)
The purpose of this study is to find out how the use of social media affects the lifestyle of students in Jekan Raya. This qualitative research uses an interview survey method and collects data by using references, journals, articles, and interview results, which include several questions about how the use of social media affects students' current lifestyle. This research shows that students spend more time on social media. Whatshapp, Tiktok, Facebook, and Instagram are the most widely used social media. In general, smartphones are used to access social media for more than five hours every day. Social media impacts lifestyles by providing information needed to complete tasks that support achievement, fulfil lifestyle needs, and follow trends. Students can overcome social media dependency by organising their time.